Gabon : Background Paper. (IMF Staff Country Reports; Country Report, 1996)
This paper provides background material to the IMF staff report for the 1995 Article IV Consultation with Gabon. It provides an overview of Gabon's economic and financial performance since independence, highlighting the five distinct phases and the economic strategies pursued by the authorities. The paper presents an overview of developments in the oil sector, and analyzes the structure of the balance of payments. The paper also reviews the public enterprise sector and its financial performance.